ANALYTICAL INVESTIGATION OF OSCILLATIONS GUY WITH KINEMATIC PERTURBATION - Volkova, V. Ye.; Misiura, Ye. O. (Science and Transport Progress, 2005)
The article examines the questions of improving supervision and diagnostic techniques of facilities. Natural frequency of superstructure is selected as a primary diagnostic parameter. Modeling of dynamic behavior of a span superstructure has been based on the finite-element method.